Evaluation of adipokine chemerin in hypertensive obese - Dalia Ramzy Ibrahim; Mervat Elsayed Taha; Amaal Mohamed Kamal (Bioscience Journal, 2019)
Chemerin is an adipokine secreted by adiopose tissue and has a role in obesity and hypertension. This study aims at assessing the level of the adipokine chemerin in obesity and/or hypertension and correlating its level with the inflammatory marker hs-CRP and predictors of atherosclerosis as lipid profile, insulin resistance, systolic (SBP) and diastolic blood pressure (DBP).Volunteers were divided into 4 equal groups according to body mass index (BMI) and blood pressure: normal weight group (BMI ≤ 24.9 kg/m2), overweight group (BMI = 25.0 – 29.9 kg/m2), normotensive obese group (BMI ≥ 30.0 kg/m2) and hypertensive obese group (BMI ≥ 30.0 kg/m2). Chemerin, high-sensitivity C-reactive protein (hs-CRP), lipid profile, fasting blood glucose (FBG) and fasting insulin (FI) were evaluated in the mentioned groups.The results showed that there were significant increases of chemerin, hs-CRP, low density lipoprotein (LDL), SBP and DBP in hypertensive obese group compared to normotensive obese , overweight and normal weight groups. Moreover the only significant positive correlation between chemerin and hs-CRP was observed in the obese hypertensive group. The normotensive obese group showed significant increases of hs-CRP, LDL, triglyceride (TG), FBG, FI and the homeostasis model assessment-insulin resistance index (HOMA-IR) compared to the overweight and normal weight groups. Regarding the overweight group, there were significant increases in chemerin, hs-CRP, cholesterol, LDL, TG compared to the normal weight group, while the HDL levels were significantly lower compared to the two obese groups. These results revealed that the pro-inflammatory adipokine chemerin increases in obesity associated with hypertension, leading to the suggestion that there is a definite dysregulation of the pro-inflammatory and anti-inflammatory parameters towards the pro-inflammatory when hypertension and obesity are associated.